Strategi Belajar dalam Perkembangan Moral untuk Program Pendidikan yang Adil - Afit Tito Purwani; M. Willian Anwar (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the learning strategies applied in developing the moral character of students through the Equivalency Education Programme as a solution to the limitations of formal education. Using a qualitative approach based on field research, this article examines the role of tutors in conveying moral values through lectures, discussions, question and answer sessions, and recitations. Psychological and socio-cultural approaches are employed to enhance the effectiveness of these strategies, supplemented by the application of habit formation, modelling, advice, and disciplinary measures. Findings indicate that the success of moral education in non-formal education pathways is influenced by the alignment of strategies with students' conditions, teachers' readiness, and curriculum flexibility. This article emphasises that character education can still be optimised outside the formal education system through structured and contextual strategies.